2020
DOI: 10.1099/mgen.0.000473
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of clinical and environmental Mucorales isolates obtained from an investigation of mucormycosis cases among solid organ transplant recipients

Abstract: Mucormycoses are invasive infections by Rhizopus species and other Mucorales. Over 10 months, four solid organ transplant (SOT) recipients at our centre developed mucormycosis due to Rhizopus microsporus (n=2), R. arrhizus (n=1) or Lichtheimia corymbifera (n=1), at a median 31.5 days (range: 13–34) post-admission. We performed whole genome sequencing (WGS) on 72 Mucorales isolates (45 R. arrhizus, 19 R. delemar, six R. microsporus, two Lichtheimia species) from these patients, from five patients with community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…Reference sequences ( Supplementary Table S1 ) from Nguyen et al (2020) were downloaded from GenBank, the evolutionary history was inferred using the Neighbor-Joining method ( Saitou and Nei, 1987 ), evolutionary analyses were conducted in MEGA7 ( Kumar et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference sequences ( Supplementary Table S1 ) from Nguyen et al (2020) were downloaded from GenBank, the evolutionary history was inferred using the Neighbor-Joining method ( Saitou and Nei, 1987 ), evolutionary analyses were conducted in MEGA7 ( Kumar et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic data are a useful resource to understand the mechanism of plant-pathogen interaction and are used in the phylogenetic analyses of the species ( Ailloud et al, 2015 ). Beyond the isolate of R. oryzae from tobacco, many strains of R. oryzae were isolated from sweet potato, mulberry, lily ( Holmes et al, 2002 ) and the human body ( Nguyen et al, 2020 ). Information obtained from the National Center for Biotechnology Information (NCBI) could be learned that a total of 43 strains of R. oryzae had been sequenced, and there were less differences of genomic data with different R. oryzae strains.…”
Section: Introductionmentioning
confidence: 99%
“…At present, our findings and those of studies showing bacterial genetic diversity at nonbloodstream sites have important implications for molecular epidemiologic investigations of infectious outbreaks and nosocomial transmission of pathogens. Data here and in our previous study of clinical and environmental Mucorales suggest caution in relying upon core genome SNP phylogeny as the sole tool in defining differences between strains ( 45 ). In both studies, comprehensive pan-genome analyses revealed variations that were not apparent with core genome SNP comparisons.…”
Section: Discussionmentioning
confidence: 73%
“…At present, our findings and those of studies showing bacterial genetic diversity at non-bloodstream sites have important implications for molecular epidemiologic investigations of infectious outbreaks and nosocomial transmission of pathogens. Data here and in our previous study of clinical and environmental Mucorales suggest caution in relying upon core genome SNP phylogeny as the sole tool in defining differences between strains (44). In both studies, comprehensive pan-genome analyses revealed variations that were not apparent with core genome comparisons.…”
Section: Discussionmentioning
confidence: 73%